Technology, climate change and forestry - Tavera Colonna, Jazmín (2015)
While Peru is known for its natural potential for forestry, little or nothing has been done for this sector. The stragglers we are in technology management in agriculture, forestry and construction sectors, strongly interrelated, has been entirely negative for the forestry sector, as the high mechanization of illegal mining. A longstanding weak regulatory framework for a state without planning capacity in a sector that represents one of the greatest riches of the country, but with strong inter sectorial linkages, prevents become one of high value added and high uptake of manpower in areas of extreme poverty. The implementation of research and technological development in this sector with inter sectorial vision is critical, since the benefits arising from this implementation will allow to obtain results in a shorter period. And it is a problem that urges us, the impact of mismanagement of forestry in climate change threatens to destroy the forest sector itself. Improvements in the regulatory framework are still pending, as well as an information system that is in full development, these advances in research and development and technology sector with integrated together allow us to reconstruct a sector with great potential for added value and effectively combat poverty.